Faedah pelaksanaan konsep bina kemudian jual kepada pembeli - Mohd. Isa, Eka Zurain (2017)
The Build Then Sell Concept (BTS) is an alternative to protect housing buyers than to suffer from the consequences of an abandoned housing projects. This method allows developers to sell residential units after project completion and already receive Certificate of Completion and Compliance (CCC). Although this method has long been implemented in developed countries, it is still less welcome among developers in the Malaysia’s housing industry. In 2007, the government had encourage a BTS implementation but there are no support to implement this method, however some developers take the initiative to implement housing projects using the BTS method in their development projects and have generated a great deal of success. Therefore, the purpose of this study is to evaluate the sales performance of BTS's residential units and the benefits of this concept to the buyer. To succeed in this study, 3 developers were selected which involved 3 projects and 118 respondents (BTS housing buyer) to obtain the relevant data. Methods of study is conducted by interviewing and using questionnaire to developers and buyers. From this study, the performance of the BTS housing sales shows that at least 50 percent of the units being sold within 3 months of launch for each housing project. The findings also shows that the implementation of BTS actually benefited to the buyer, especially the physical benefits.